Long-run trends in earnings and employment in Hungary, 1972-1996 - Arpad Abraham; Gabor Kezdi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2000)
Transition from socialist to capitalist economy led to enormous changes in earnings and employment. In our study a long-horizon descriptive analysis is presented about the major trends, including the last fifteen years of socialism. Education, gender, calendar time, age and vintage effects are separately analyzed. Aggregate (quasi-) panel analysis is used to assess the role of labor demand and labor supply, concluding that exogenous supply factors explained most of what happened before the transition, while the transition itself was dominated by large labor demand shocks. These demand shocks are in large part structural, as opposed to cyclical, and are highly correlated with vintage, gender and education. The main results are summarized in a list of stylized facts.
Keywords: 330